2021
DOI: 10.1038/s41467-021-21358-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in mobility and COVID-19 transmission

Abstract: In response to the COVID-19 pandemic, countries have sought to control SARS-CoV-2 transmission by restricting population movement through social distancing interventions, thus reducing the number of contacts. Mobility data represent an important proxy measure of social distancing, and here, we characterise the relationship between transmission and mobility for 52 countries around the world. Transmission significantly decreased with the initial reduction in mobility in 73% of the countries analysed, but we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
406
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(488 citation statements)
references
References 33 publications
23
406
0
6
Order By: Relevance
“…Our results are similar to previously reported R 0 in China [ 17 , 27 ] and neighboring country India [ 28 ]. After a week of nation-wide lockdown, R t decreased substantially from early April 2020 in Bangladesh, which corroborates with those of [ 29 , 30 ]. Our finding suggests that Bangladesh has seen an upheaval of R t in early February 2021, which corroborates with Abbott et al [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Our results are similar to previously reported R 0 in China [ 17 , 27 ] and neighboring country India [ 28 ]. After a week of nation-wide lockdown, R t decreased substantially from early April 2020 in Bangladesh, which corroborates with those of [ 29 , 30 ]. Our finding suggests that Bangladesh has seen an upheaval of R t in early February 2021, which corroborates with Abbott et al [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Our research has revealed that it is more relevant to look for a relationship between human mobility and Covid-19 transmission adopting a 14-day moving average. This observation is important, because much of the previous research into the impact of mobility reduction on Covid-19 transmission was based on smoothing data streams by using the 7-days rolling averaged mobility, leading to a significant difference in correlation analysis results [ 53 , 54 ]. This also applies to the sample size, which for the mentioned studies was 52 countries.…”
Section: Discussionmentioning
confidence: 99%
“…[27] For this, mobility data were obtained from a mobile phone-based panel survey, whose participants were representative of the population by age, gender and region. Our research on the link between mobility and COVID-19 spreading extends beyond previous studies [10][11][12][13][14][15][16][17][18] by comparing the effect of mobility in two different waves.…”
Section: Discussionmentioning
confidence: 55%
“…Previous work found a positive association between mobility and transmission in the first wave but it was suspected for many countries worldwide that a decoupling in the relationship took place afterwards. [18][19][20] Our results suggest that human mobility is an important determinant for explaining reductions in SARS-CoV-2 transmission during both the first and the second wave in Switzerland. We found that the effect of a 1 % reduction in average daily travel distance on the effective reproduction number was of similar magnitude in both waves.…”
mentioning
confidence: 67%